2017
DOI: 10.7863/ultra.16.06002
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the International Endometrial Analysis Group Color Score for Assigning the Amount of Flow Within the Endometrium Using Stored 3-Dimensional Volumes

Abstract: The reproducibility of assigning the IETA color score for assessing endometrial vascularization using 3-dimensional volumes is good or very good regardless of the experience of the examiner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In most benign lesions, the color score was ≤2 points, while, the color score was ≥3 points in most malignant lesions. The results of Alcazar et al (17) was similar to ours. Meanwhile, Alcazar et al confirmed that the reproducibility of assigning the IETA color score for assessing endometrial vascularization using three-dimensional volumes was good regardless of the experience of the examiner.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In most benign lesions, the color score was ≤2 points, while, the color score was ≥3 points in most malignant lesions. The results of Alcazar et al (17) was similar to ours. Meanwhile, Alcazar et al confirmed that the reproducibility of assigning the IETA color score for assessing endometrial vascularization using three-dimensional volumes was good regardless of the experience of the examiner.…”
Section: Discussionsupporting
confidence: 89%
“…Early diagnosis of benign and malignant lesions in uterine cavity or endometrium is of great significance for early clinical treatment and improvement of prognosis (2,38). The imaging examinations are important methods, especially transvaginal ultrasonography (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology employed in this investigation is consistent with that of the International Endometrial Tumor Analysis collaborative group. 15,16 The clinical importance of these methodologies should be recognized for the impact they can have on patient care, since there is often difficulty in properly obtaining a diagnosis of EC when it presents as PMB. 17,18 An example of this situation is when cervical stenosis is encountered, which can prevent histologic sampling of the endometrium, as was encountered in this case series.…”
Section: Discussionmentioning
confidence: 99%